From METS to malaria: RRx-001, a multi-faceted anticancer agent with activity in cerebral malaria - Yalcin, Ozlem (2015)
University of California. Department of Bioengineering. San Diego, CA, USA / Koç University. School of Medicine. Istanbul, Tirkey.